MEKANISME GOOD CORPORATE GOVERNANCE DALAM MENEKAN TINDAKAN KECURANGAN PADA PERUSAHAAN GO GREEN DI INDONESIA - Lukman Ibrahim; Hidayat Darwis; Supriatiningsih Supriatiningsih (STIE Muhammadiyah Jakarta, 2022)
Fraud is an act to gain profit through asset misappropriation, manipulation of financial statements and corruption. Fraud by manipulating financial statements has a lower intensity than fraud in the form of asset abuse and corruption, but has a very large loss impact. This study aims to measure whether corporate governance can reduce the level of financial statement fraud with the triangle model. The independent variables are pressure, opportunity, rationalization and the dependent variable is financial statement fraud. The population in this study are companies listed on the Sri Kehati stock index of the Indonesia Stock Exchange (IDX) in 2017-2021. The data analysis technique uses multiple linear regression. The results of the analysis of this study are that there is a positive and significant influence between financial stability, Ineffective Monitoring (BDOUT) Rationalization (TATA) on financial statement fraud. There is a negative and significant influence between External Pressure (LEV), Personal Financial (Oship) Financial Target (ROA) on fraudulent financial statements. There is no influence between the Nature of Industry (REV), the Audit Committee (KA) on fraudulent financial statements. The audit committee is able to weaken the effect of rationalization on financial statement fraud. The audit committee is able to strengthen the effect of rationalization on fraudulent financial statements. The audit committee was unable to moderate the effect of External Pressure (LEV) on fraudulent financial statements. The audit committee was unable to moderate the effect of financial targets on fraudulent financial statements. The audit committee is not able to moderate the effect of inefficient monitoring on financial statement fraud.